Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1086/524888
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium knowlesi Malaria in Humans Is Widely Distributed and Potentially Life Threatening

Abstract: Human infection with P. knowlesi, commonly misidentified as the more benign P. malariae, are widely distributed across Malaysian Borneo and extend to Peninsular Malaysia. Because P. knowlesi replicates every 24 h, rapid diagnosis and prompt effective treatment are essential. In the absence of a specific routine diagnostic test for P. knowlesi malaria, we recommend that patients who reside in or have traveled to Southeast Asia and who have received a "P. malariae" hyperparasitemia diagnosis by microscopy receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
615
1
42

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 727 publications
(686 citation statements)
references
References 16 publications
11
615
1
42
Order By: Relevance
“…falciparum is the malarial species that is the most important cause of mortality in humans but, in addition, nearly 3 billion people, mainly in Asia and South America, are at risk from another malaria species, P. vivax, which causes chronic disease and deadly complications (Guerra et al, 2010). Three more species, P. ovale, P. malariae and P. knowlesi (Cox-Singh et al, 2008) can also cause malaria in humans. Infections with malaria may reach very high levels, for example, Mueller et al (2009) found that 73% of a Papua New Guinea population were infected.…”
Section: General Backgroundmentioning
confidence: 99%
“…falciparum is the malarial species that is the most important cause of mortality in humans but, in addition, nearly 3 billion people, mainly in Asia and South America, are at risk from another malaria species, P. vivax, which causes chronic disease and deadly complications (Guerra et al, 2010). Three more species, P. ovale, P. malariae and P. knowlesi (Cox-Singh et al, 2008) can also cause malaria in humans. Infections with malaria may reach very high levels, for example, Mueller et al (2009) found that 73% of a Papua New Guinea population were infected.…”
Section: General Backgroundmentioning
confidence: 99%
“…In such circumstances, non-invasive sampling and the application of molecular tools can provide data which, in the past, were only available following opportunistic necropsy. For example, from an anthropocentric viewpoint, an understanding of the species of Plasmodium affecting primates in the wild led to the identification of a new zoonosis, with P. knowlesi found in humans using molecular tools [132,133]. In contrast, the application of molecular tools has identified a novel, genetically distinct form of Leishmania in macropod marsupials in Australia, as well as a new non-sandfly vector [134][135][136].…”
Section: Wildlife and Zoonosesmentioning
confidence: 99%
“…P. malariae cases are generally asymptomatic and chronic with low parasitic levels with mostly less than 5000 parasites per ll of blood. Cox-Singh et al (2008) reported 4 deaths (1.8%) in Sarawak and William et al (2011) reported deaths and several patients (39%) with severe malaria having respiratory distress, acute renal failure, and shock from a tertiary hospital in Sabah, Malaysia. But none of the patients went into coma.…”
Section: Clinical Symptoms Of P Knowlesi Infections and Treatmentmentioning
confidence: 99%